CORRELATION STUDIES IN SOME OF THE GERMPLASM LINES OF KHARIF SORGHUM - V. V. KALPANDE,; R. B. GHORADE,,; S. B. THAWARI,; Y. G. KEDAR, (The Bioscan, 2015)
Sixty three genotypes consisting of sixty germplasm lines and three improved released varieties of kharif sorghum were evaluated and correlation coefficient were estimated for the grain yield and some of the yield contributing traits including the grain mold rating. Correlation studies revealed that the character grain yield per plant showed positive and significant association with vigour index mass (0.507), vigour index length (0.486), germination percentage of seed (0.482), panicle length (0.402), root length (0.338), shoot length (0.310) and 1000 seed weight (0.181). On the other hand, specific gravity (-0.398), number of leaves (-0.280), electrical conductivity (-0.187) and threshed grain mold rating (-0.150) showed negative and significant correlation with grain yield per plant. The importance should be given to plant height and number of leaves in developing high fodder yielding varieties in sorghum. Similarly seed hardness should be taken in to consideration for improvement in the germination percentage of seed